Psychological distress and compliance with sanitary measures during the Covid-19 pandemic - Irwin Hecker; Solène Wallez; Honor Scarlett; José Luis Ayuso-Mateos; Richard Bryant; Giulia Caggiu; Claudia Conflitti; Katalin Gémes; Josep Maria Haro; Vincent Lorant; Roberto Mediavilla; Ellenor Mittendorfer-Rutz; et al. (PLoS ONE, 2025)
Background This study aims to understand the relationship between the experience of psychological distress and compliance with COVID-19 sanitary measures. We testeed whether this relationship was modified by individuals’ gender and socioeconomic status (i.e., educational level and employment). Methods Data from four European cohort studies (n = 13,635), were analysed using an Individual Participant Data (IPD) meta-analytic approach. Mixed effect models were employed to examine associations between mental health difficulties and compliance with sanitary measures, as well as effect modification by socioeconomic status. Statistical models were stratified by gender. Results We found a statistically significant association between mental health difficulties and increased compliance with sanitary measures in women, while amongst men the statistically significant association observed was opposite. Moreover, there was a statistically significant interaction between participants’ educational level and mental health difficulties amongst men only, indicating especially low compliance levels with COVID-19 sanitary measures amongst individuals with only primary schooling and who reported psychological distress. Conclusion The association between psychological distress and compliance with sanitary measures is complex–positive in women, negative in men. Men experiencing mental health difficulties, especially those with lower educational attainment, exhibit low levels of compliance with sanitary measures. These results suggest that psychological distress and its possible consequences should be considered when designing measures addressing infectious disease spread.